(untitled) (Iter, 2022)
The question about the relations between truth and delusion is stated, since the latter cannot be simply conceived as an error. The traditional concept o f truth as adaequatio intellectus rei is analyzed, as well as the extraordinary contribution to the subject by Martin Heidegger, when he proposes to conceive the truth as dis-covery (a-létheia) and as liberty (for letting things be what they are). Then the fundamental role o f the other in the happening o f truth is postulated. The thesis o f the inter-subjective foundation o f truth is illustrated by way o f the description o f a case o f erotomania where, by definition, the other does not particípate o f ñor even knows about such loving relationship. The characteristics o f this “delusional truth ” are analyzed, among which the authenticity and radicalness showed by delusional patients andparticularly schizophrenics in their approximation to the world and to the things are singled out. Finally, the author attempts to demónstrate that delusion has everything in common with the happening o f truth, only that the other does not particípate in its constitution.